2018
DOI: 10.1103/physrevd.98.123016
|View full text |Cite
|
Sign up to set email alerts
|

Fast radio bursts from primordial black hole binaries coalescence

Abstract: In this paper we propose the model that the coalescence of primordial black holes (PBHs) binaries with equal mass M ∼ 10 28 g can emit luminous gigahertz (GHz) radio transient, which may be candidate sources for the observed fast radio bursts (FRBs), if at least one black hole holds appropriate amount of net electric charge Q. Using a dimensionless quantity for the charge q = Q/ √ GM , our analyses infer that q ∼ O(10 −4.5 ) can explain the FRBs with released energy of order O(10 40 )ergs. With the current sam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 84 publications
0
37
1
Order By: Relevance
“…Numerous phenomenological scenarios were proposed for PBH formation and, especially, for PBH generation after inflation in the early Universe, under the assumption that PBHs contribute to DM (see e.g., Refs. [14][15][16][17][18][19][20] and the references therein). Indeed, the whole PBH DM case leaves only two limited windows for allowed PBH masses around either 10 −15 or 10 −12 of the Solar mass.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous phenomenological scenarios were proposed for PBH formation and, especially, for PBH generation after inflation in the early Universe, under the assumption that PBHs contribute to DM (see e.g., Refs. [14][15][16][17][18][19][20] and the references therein). Indeed, the whole PBH DM case leaves only two limited windows for allowed PBH masses around either 10 −15 or 10 −12 of the Solar mass.…”
Section: Introductionmentioning
confidence: 99%
“…Up to date, over 100 FRBs have been reported in the literature and collected in FRB Catalogue 1 . Meanwhile, to explain this radio phenomena, dozens of progenitor models involved in compact objects have been proposed (Kashiyama et al 2013;Falcke & Rezzolla 2014;Lyubarsky 2014;Geng & Huang 2015;Dai et al 2016;Gu et al 2016;Wang et al 2016;Zhang 2014Zhang , 2016Zhang , 2017Lyutikov et al 2016;Metzger et al 2017;Beloborodov 2017;Deng et al 2018;Margalit & Metzger 2018;Metzger et al 2019;Beloborodov 2019), accounting for non-repeating and/or repeating FRBs. A full model list can refer to Platts et al (2019)…”
Section: Introductionmentioning
confidence: 99%
“…When estimating the luminosity of the cCBC signal, Zhang (2016) considered the magnetic dipole radiation power by analogy with pulsars. Deng et al (2018) noticed that for a cCBC system, electric dipole radiation is actually more significant. We treat the electric dipole radiation following Deng et al (2018) in this subsection.…”
Section: Electric Dipole Radiation Luminositymentioning
confidence: 99%
“…He further suggested that with a smaller charge, BH-BH merger systems may account for a fraction of non-repeating fast radio bursts (FRBs), the mysterious millisecond radio bursts at cosmological distances (Lorimer et al 2007;Thornton et al 2013). The charged BH-BH mergers were invoked in several other studies to account for the EM counterparts of BH-BH mergers or FRBs (Liebling & Palenzuela 2016;Liu et al 2016;Deng et al 2018;Fraschetti 2018;Levin et al 2018). Whether BHs can sustain a significant amount of charge is still an open question.…”
Section: Introductionmentioning
confidence: 99%